Environmental sustainability of light-driven processes for wastewater treatment applications. (1st May 2018) - Foteinis, Spyros; Borthwick, Alistair G.L.; Frontistis, Zacharias; Mantzavinos, Dionissios; Chatzisymeon, Efthalia
Abstract: A comparative analysis is presented of light-driven advanced oxidation processes in terms of environmental sustainability. Photochemical oxidation has proven a viable option for treating emerging and priority pollutants at laboratory scale. Nevertheless, as a nascent technology, photocatalysis is yet to be widely applied at large-scale water treatment plants. This paper presents a powerful tool that should enable stakeholders to develop sustainable, large-scale, photocatalytic treatment plants by providing knowledge of environmental sustainability and hotspots (where technological flaws have high environmental impact) and understanding as to how process sustainability can be improved through scenario analyses. The following processes were examined: natural and simulated solar photolysis, solar photo-Fenton without hydrogen peroxide addition (solar/Fe), solar photo-Fenton (solar/Fe/H2 O2 ), photolysis under UV-A irradiation (UV-A), titania-mediated photocatalysis (UV-A/TiO2 ), photolysis under UV-C irradiation (UV-C), and UV-C treatment with hydrogen peroxide addition (UV-C/H2 O2 ). Actual life cycle inventory data were collected at bench scale, and the environmental performances estimated by means of life cycle assessment. Effective removal of 1 μg of 17α-ethynylestradiol per liter of wastewater, a commonly occurring micropollutant and endocrine disrupting chemical, was used as the functional unit. Solar photolysis exhibited an environmental footprint about 23 times higher than solar/Fe. Solar/Fe/H2 O2 minimized the environmental footprint. Being energy intensive, simulated solar irradiation had a much higher (∼5-fold) environmental footprint than natural solar light. UV photolysis exhibited low environmental impact, with UV-C found to be about 3 times more environmentally friendly than UV-A photolysis. Addition of TiO2 to UV-A and H2 O2 to UV-C caused their total environmental impacts to decrease by about 97% and 88%, implying that UV-A/TiO2 was better than UV-C/H2 O2 . In terms of total environmental footprint, the advanced oxidation processes descend in the following order: solar photolysis > UV-A > UV-C > solar/Fe > UV-A/TiO2  > UV-C/H2 O2  > solar/Fe/H2 O2 . The environmental sustainability of all processes was directly proportional to treatment efficiency but inversely proportional to treatment time (due to the large energy input per unit time). Although reagent use (i.e. titania, iron, and hydrogen peroxide) was not associated with high environmental impact, its addition greatly improved process efficiency as well as environmental sustainability. For all examined light-driven processes, the main environmental hotspot was electricity consumption. Introduction of renewable energy sources could reduce the environmental footprint of oxidation processes by up to 87.5%. Highlights: LCA was utilized to assess the environmental footprint of light-driven processes. Solar/Fe/H2 O2 was the most environmentally friendly technique for water treatment. Treatment time is an important parameter that can affect environmental sustainability. The main hotspot in all examined technologies was electricity consumption. The use of renewable energy sources can increase environmental sustainability by 87.5%.